Analysis of the Predicted Number of HIV/AIDS Spreads in Sidoarjo Regency using Multiple Linear Regression Method - Azizah, Risma Nur; Indahyanti, Uce (Indonesian Journal Publisher, 2024)
The Office of Communication and Information of East Java Province, which includes Sidoarjo Regency, is one of the data sources used to determine the fourth-highest number of HIV/AIDS cases in Indonesia. The aim of this study is to forecast an annual increase in the number of HIV/AIDS patients in Sidoarjo Regency. The Sidoarjo District Health Office is the private source of data used in this study. The information utilized spans the years 2020–2022, and it contains attributes with projected results of positive HIV/AIDS patients. The estimated number for 2023 is 795,667; for 2024, it is 934,167; and for 2025, it is 1072,667. Because there are numerous attribute data sets obtained, quick miner processes the data using multiple linear regression as the chosen approach. The root mean squared error (RSME) validation test yielded a performance score of 0.816 for the multiple linear regression model, indicating that a smaller prediction result indicates greater validity.